PENGARUH INFLASI DAN TINGKAT PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI INDONESIA PERIODE 2012-2024 - Syafna Malikhatus Shofia; Lifia Revanata; Nazilia Putri Altifa; Agus Eko Sujianto (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of inflation and unemployment rates on poverty levels in Indonesia during the period 2012-2024. The background of this study is based on fluctuations in macroeconomic indicators and poverty dynamics that show significant changes, especially during the COVID-19 pandemic. The research method uses a quantitative approach with an associative design, using secondary data from BPS and Bank Indonesia, which is analyzed through multiple linear regression. The results show that inflation and unemployment rates simultaneously have a significant effect on poverty levels. However, partially, only the unemployment rate has been proven to have a significant effect, while inflation has no significant effect on poverty changes during that period. These findings indicate that unemployment is the most decisive macroeconomic factor in influencing poverty levels. This study emphasizes the importance of job creation policies and strengthening the productive sector in poverty alleviation efforts in Indonesia.Keywords— inflation, unemployment rate, poverty rate, macroeconomics.